Species Composition and Economic Evaluation under Agroforestry Practices in three districts of Haryana - Singh, Rambir; Singh, Charan; Gulati, Ajay (Indian Forester, 2022)
The study is the outcome of status and economic evaluation of poplar, eucalyptus and other species based agroforestry practices adopted by farmer in Ambala, Kurukshetra and Yamunanagar districts of Haryana. The Populus deltoides and Eucalyptus spp. were dominant commercial species of agroforestry systems followed. Block plantation was adopted highest in Kurukshetra followed by Yamunanagar and Ambala while boundary plantations were also found highest in Ambala than Yamunanagar and Kurukshetra. Among species, poplar was major component in Yamunanagar followed by Ambala and Kurukshetra and Eucalyptus had major composition in Kurukshetra than Ambala and Yamunanagar. Among horticulture species, mango, guava etc. were found maximum in Yamunanagar followed by Ambala and Kurukshetra while the forestry species like neem, drek, shisham etc were also found in the trend of Yamunanagar, Kurukshetra and Ambala districts. The overall net return was found higher under block system than the bund system in poplar based agri-silviculture system. In commercial terms, the B:C ratio was found higher from Poplar based in block planting than poplar based on bund planting in agri-silviculture system. Similarly, net returns were also obtained from eucalyptus based agroforestry systems. Comparatively as per net returns and B:C ratio in the block system were found more economic to bund systems.